Tradisi Tahlilan Upaya Menyambung Silaturahmi - Andi Warisno (Ri'ayah: Jurnal Sosial dan Keagamaan, 2017)
Indonesia is a unitary State of diversity. Indonesia consists of a wide range of cultures, regional languages, races, ethnic groups, religions and beliefs, etc. However, Indonesia is able to unify the various diversity in accordance with the slogan of the Indonesian nation "Bhineka Tunggal Ika", which means different but still one. Unity and unity was realized thanks to the strong defense of indigenous culture of the nation of Indonesia. Culture that has long been inherent in the body of the Indoseia a lot in the form of traditions that continue to be maintained. Tradition is something that has been done for a long time and become part of the life of a community group which is one of the real manifestation of the spirit of unity of Indonesian society. In life with the surrounding community, people recognize various experiences, customs, traditions or cultures. From these experiences and traditions people realize that as human beings can not live alone, but need others and must help each other. And this is where the function of tradition, custom or culture as adhesive between citizens as well as efforts to maintain harmony among / interns of religious communities. Every society has its own social system and cultural system that distinguishes it from other societies. Society has a number of traditions or customs that are still carried out in certain events or specific circumstances and also passed on to the next generation. The tradition is viewed by the society is still functional and as a religious ritual that is worthy of worship even social and in accordance with the demands of the environment where people live. One of the local wisdom or traditions that is still maintained and persisted to the present day in society is the "Tahlilan tradition".